2006
DOI: 10.2514/1.15556
|View full text |Cite
|
Sign up to set email alerts
|

Civil-Transport Wing Design Concept Exploiting New Technologies

Abstract: Current trends in the design of transport aircraft have shown that in order to be economically viable and competitive it is necessary to investigate technologies which may give an improvement in performance and operational flexibility goal, but must be shown to be cost-effective. The current competitive environment forces the airlines to buy advanced technology aircraft and requires manufacturers to provide more operational flexibility, without drastic performance penalties. This is a challenging task, which m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…The initial studies of VCCTEF have been conducted by deploying it on the airframe of the GTM wing. Edi et al [16] reviewed the new technologies related to the wing design of civil-transport aircraft and had considered the combination of HLFC-VCW on the wing of advanced technology regional aircraft (ATRA) [19]. The present work reports the combination of HLFC-VCCTEF on ATRA wing's outboard airfoil.…”
Section: Present Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial studies of VCCTEF have been conducted by deploying it on the airframe of the GTM wing. Edi et al [16] reviewed the new technologies related to the wing design of civil-transport aircraft and had considered the combination of HLFC-VCW on the wing of advanced technology regional aircraft (ATRA) [19]. The present work reports the combination of HLFC-VCCTEF on ATRA wing's outboard airfoil.…”
Section: Present Workmentioning
confidence: 99%
“…There can be a loss of laminar flow if there is a variation in lift coefficient and Mach number due to the change in the designed pressure distribution. A combination of HLFC and Variable Camber Wing (VCW) techniques suggested that the variable camber (flap deflection at a low angle of attack) can maintain the designed pressure distribution at off-design conditions, to obtain an optimum benefit [16].…”
Section: Techniques For Increasing Aerodynamic Efficiencymentioning
confidence: 99%
“…In order to maintain laminar flow, and to improve optimization efficiency, the quantity of the FPG, denoted as Q FPG = −dC p /dX, are applied in the optimization. On the front part of airfoil, where X < 0.50, for both upper and lower surfaces Q FPG should be larger than 0.0. dC p /dX is limited to be less than 3.0 on the pressure recovery region ( X > 0.70) to avoid trailing edge separation [8]. …”
Section: Airfoil Optimization With Pressure Distribution Constraintmentioning
confidence: 99%
“…Laminar flow length could be achieved through maintaining Favorable Pressure Gradient (FPG, or negative pressure gradient) [8]. However, the FPG should not be so great as to avoid excessive shock strength [8]. Nevertheless, the quantitative influence of FPG on drag of supercritical NLF airfoil is not so clear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation